2018
DOI: 10.3390/molecules23123211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Low-Toxic Formulation Development of Glycosylated Paclitaxel Prodrugs

Abstract: Paclitaxel (PTX) is a famous anti-cancer drug with poor aqueous solubility. In clinical practices, Cremophor EL (polyethoxylated castor oil), a toxic surfactant, is used for dissolution of PTX, which accounts for serious side effects. In the present study, a single glucose-conjugated PTX prodrug (SG-PTX) and a double glucose-conjugated PTX prodrug (DG-PTX) were synthesized with a glycosylated strategy via succinate linkers. Both of the two prodrugs presented significant solubility improvement and drug-like lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…4), where the glucose moieties were attached via succinate linkers. 70 Both prodrugs showed improved aqueous solubility and drug-like lipophilicity over the parent drug. Of the two, the single glucose conjugate 15a had a more efficient release in serum, where a high percentage of the parent drug was detected following hydrolysis with β-glucuronidase.…”
Section: Glycosidase Activated Prodrugsmentioning
confidence: 99%
“…4), where the glucose moieties were attached via succinate linkers. 70 Both prodrugs showed improved aqueous solubility and drug-like lipophilicity over the parent drug. Of the two, the single glucose conjugate 15a had a more efficient release in serum, where a high percentage of the parent drug was detected following hydrolysis with β-glucuronidase.…”
Section: Glycosidase Activated Prodrugsmentioning
confidence: 99%
“…In another study, glycoconjugates of paclitaxel with single or double glucose moieties attached by succinate linkers were reported [ 74 ]. Both the C-2′-single glycosylated paclitaxel (GluSA-PTX) and the double glycosylated paclitaxel ( bis -GluSA-PTX) conjugates showed effective cytotoxicity against breast cancer cells and improved hydro solubility compared to the parent drug.…”
Section: Glycoconjugatesmentioning
confidence: 99%
“…There is high inter- and intra-species variability in taxane content [ 25 , 26 ], and it has been shown that this variability can depend on the season and taxoid type. The concentration of 10-DAB in first- and second-year needles of T. baccata grown in a Polish garden was highest in January and lowest in April [ 3 ], while in a study in Tehran, Iran [ 6 ], the highest concentration in yew needles was reached in August. The bark of T. baccata grown in the forests of the Czech Republic showed that the highest concentration of PTX and three other taxanes was in October and the lowest in January [ 27 ].…”
Section: Taxus Spp and Biologically Active Compoundsmentioning
confidence: 99%
“…PTX concentration in T. cuspidata, T. media, and T. mairei is 1.67, 1.22, and 0.66 mg/g, respectively. Paclitaxel (Taxol A) was isolated from Taxus plants and has been widely used since 1984 in the treatment of various cancers (mainly tumours of the breast, ovaries, pancreas or stomach) [ 4 ], while in order to improve the effect, new ways of administering this drug are constantly being developed [ 5 , 6 , 7 , 8 , 9 ]. The reason is mainly the achievement of a better biological effect in the exact target place in different types of tissues [ 10 , 11 ] with the least possible number of side effects and at the same time bypassing various resistant mechanisms of tumour cells (overexpression of multidrug resistance (MDR) efflux transporters or by microtubule alterations) [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%